Environmental Vulnerability of Urban Trees. Georeferenced Survey at the District Level, Chile [Vulnerabilidad Ambiental del Arbolado Urbano. Levantamiento Georreferenciado Comunal, Chile] - Carbonnel-Torralbo, A (Universidad Austral de Chile, 2017)
Based on a tree register made during June to September 2014, this study discusses the environmental vulnerability of public urban trees (EVPUT) in the district of Providencia, Santiago, Chile. The variables considered in the analysis are Growth Phase, Plant Health Status, and Biotic Stress Status, which combined in an assessment matrix show considerable spatial differences regarding vulnerability. Considering the entire study area, the most representative species were Acer negundo L., Robina pseudoacacia L., and Platanus orientalis L. (50% of total tree population). The first two species are highly vulnerable, which is shown in the EVPUT map designed with a Geographic Information System s open code software. The results aim at improving the commune s urban environmental management.